THE INFLUENCE OF USING MEDIA FUN THINKER BOOK TO INCREASE ENGLISH LANGUAGE VOCABULARY IN EARLY CHILDHOOD EDUCATION : Quasi-experimental method in TK Islam TerpaduSenyumAnanda Bandung - Budhiarti, Nova (2014)
This research is motivated by the progress of this era of globalization where language proficiency is required not to mention foreign language skills in this case English. Leaning English for understanding English vocabulary can be done by using media managed to significantly improve English vocabulary early childhood? That is the formulation of the problem in this thesis. The general objective of this study was to determine the level of English proficiency before and after treatment with either treatment using fn thinker book's media for the experimental group and flashcard media for control group in TK SenyumAnanda. This study used a quasi-experimental method and non-participatory technique with checklist and interval scale. Based on the calculation., that each value t-count > - ttable and p-value>0.05. Because the p.value>0.05, it can be concluded that there is no English vocabulary before and after treatment between the experimental group and control group. The result of this study mentions no significant effect on the improvement of theEnglish vocabulary of early childhood using fun thinker book. In the experimental group after treatment showed a very good indication of the amount to 12.5 while the control group amounted to 27.3. category well and being in experimental group were in balanced position in 43.8 while, both categories in the control group were as uch as 54.5 and 18.2. the things that influence is a lack of tme and lack of research subjects observation that the authors recommend for further research on an extension of the study period and increasing the number of sample. Penelitianinidilatarbelakangiolehkemajuan era globalisasisekarangini di manakemampuanberbahasasangatlahdiperlukantakterkecualikemampuanberbahasaasingdalamhalinibahasaInggris.PembelajaranbahasaInggrisuntukmenguasainkosakatabahasaInggrisbisadilakukandenganmenggunakan media fun thinker book. Namunapakah media iniberhasilsecarasignifikanmeningkatkankosakatabahasaInggrisanakusiadini? Itulah yang menjadiperumusanmasalahdalamskripsiini.AdapuntujuanumumdaripenelitianiniadalahuntukmengetahuitingkatpenguasaanbahasaInggrissebelumdansetelahtreatment baikperlakuandenganmenggunakan media fun thinker book ataupun media kartu kata padakelompokeksperimendan control padaanak-anak TK Islam TerpaduSenyumAnanda. Penelitianinimenggunakanmetodekuasieksperimenmenggsunakantekhnikobservasi non parsipatorisdengantekhnikcheck list denganskala interval. Berdasarkan hasil perhitungan diperoleh bahwa masing-masing nilai - thitung > - ttabel dan nilai p-value > 0,05. Karena nilai p-value > 0,05, maka dapat disimpulkan bahwa tidak terdapat penguasaan kosakata Bahasa Inggris sebelum dan setelah perlakuan antara kelompok eksperimen dan kelompok kontrol. Hasilpenelitianinimenyebutkantidakadapengaruh yang signifikanterhadappeningkatankosakatabahasaInggrisanakusiadinidenganmenggunakanfun thinker book. Pada kelompok eksperimen setelah perlakuan menunjukkan indikasi sangat baik berjumlah 12.5 sedangkan kelompok kontrol berjumlah 27.3. Kategori baik dan sedang pada kelompok eksperimen berada di posisi seimbang yaitu 43.8 sedangkan, kategori baik pada kelompok kontrol sebanyak 54.5 dan sedang sebanyak 18.2. Adapun hal-hal yang mempengaruhinya adalah kurangnya waktu observasi dan kurangnya subjek penelitian sehingga penulis merekomendasikan untuk peneliti selanjutnya tentang adanya perpanjangan masa penelitian dan menambah jumlah sampel.